Experimental study the anti-inflammatory and osteo-regenerative qualities of the paste based on symphytum officinale tincture and calcium hydroxide - Iryna Kostyiuk; Victor Kostiuk; Halyna Kimak; Yuriy Oktysyuk; Lilia Tarnavska (Pensoft Publishers, 2021)
Replacement of the damaged bone remains actual and is far from being completely solved nowadays, despite its centuries-old history. The purpose of study was to investigate the anti-inflammatory and osteo-regenerative qualities of the paste based on Symphytum officinale tincture and calcium hydroxide in treatment on teeth with chronic granulating apical periodontitis in children and in an experiment on animals. Performed morphological and densitometric studies showed that remodeling of bone injury of the lower jaw in rats occurs almost equally in both experimental and control groups, and a paste based on Symphytum officinale tincture and calcium hydroxide also promotes bone regeneration at the defect site and stimulates osteosynthesis. Analysis of liver tissue, soft and hard tissues of the lower jaw in animals suggest that the proposed paste does not produce any toxic effect and provides significant anti-inflammatory properties. The gained result provide grounds to recommend the developed paste for therapeutic use in children as a temporary root canal sealing material in permanent teeth with granulating apical periodontitis.